Physico-chemical approach to adhesion of Alicyclobacillus cells and spores to model solid materials - Strejc, Jan; Kyselova, Lucie; Cadkova, Anna; Potocar, Tomas; Branyik, Tomas (Extremophiles, 2019)
Acidothermophilic bacteria of the genus Alicyclobacillus are frequent contaminants of fruit-based products. This study is the first attempt to characterize the physico-chemical surface properties of two Alicyclobacillus sp. and quantify their adhesion disposition to model materials [diethylaminoethyl (DEAE), carboxyl- and octyl-modified magnetic beads] representing materials with different surface properties used in the food industry. An insight into the mechanism of adhesion was gained through comparison of experimental adhesion intensities with predictions of a colloidal interaction model (XDLVO). Experimental data (contact angles, zeta potentials, size) on interacting surfaces (cells and materials) were used as inputs into the XDLVO model. The results revealed that the most significant adhesion occurred at pH 3. Adhesion of both vegetative cells and spores of two Alicyclobacillus sp. to all materials studied was the most pronounced under acidic conditions, and adhesion was influenced mostly by electrostatic attractions. The most intensive adhesion of vegetative cells and spores at pH 3 was observed for DEAE followed by hydrophobic octyl and hydrophilic carboxyl surfaces. Overall, the lowest rate of adhesion between cells and model materials was observed at an alkaline pH. Consequently, prevention of adhesion should be based on the use of alkaline sanitizers and/or alkaline rinse water.
Keywords: Cell adhesion; povrchové vlastnosti; Model materials; Surface Properties; Alicyclobacillus; XDLVO model; spory bakteriální; Spores, Bacterial; Hydrogen-Ion Concentration; bakteriální adheze; Alicyclobacillus sp.; Bacterial Adhesion; Surface interaction; koncentrace vodíkových iontů